2017
DOI: 10.1007/s10646-017-1873-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular responses of adult zebrafish after exposure to CuO nanoparticles or ionic copper

Abstract: Due to their antimicrobial, electrical and magnetic properties, copper nanoparticles (NPs) are suitable for a vast array of applications. Copper can be toxic to biota, making it necessary to assess the potential hazard of copper nanomaterials. Zebrafish (Danio rerio) were exposed to 10 µg Cu/L of CuO NPs of ≈100 nm (CuO-poly) or ionic copper to compare the effects provoked after 3 and 21 days of exposure and at 6 months post-exposure (mpe). At 21 days, significant copper accumulation was only detected in fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
2
4
0
1
Order By: Relevance
“…The main histopathological alterations in the gill tissue of the dwarf cichids were lamellar epithelium lifting, hyperplasia, and hypertrophy, which were more frequent in the nCuO treatment. Similar branchial damage has been observed in rainbow trout and zebrafish after exposure to nCuO (Al-Bairuty et al, 2013;Vicario-Parés et al, 2018). Additionally, SEM images revealed some particles in the surface of the gill epithelium only in the treatment with nCuO, which may be assumed to be nanoparticle aggregations (Fig.…”
Section: The Strategies Of Mitochondrial Coupling Respiration To Copesupporting
confidence: 72%
“…The main histopathological alterations in the gill tissue of the dwarf cichids were lamellar epithelium lifting, hyperplasia, and hypertrophy, which were more frequent in the nCuO treatment. Similar branchial damage has been observed in rainbow trout and zebrafish after exposure to nCuO (Al-Bairuty et al, 2013;Vicario-Parés et al, 2018). Additionally, SEM images revealed some particles in the surface of the gill epithelium only in the treatment with nCuO, which may be assumed to be nanoparticle aggregations (Fig.…”
Section: The Strategies Of Mitochondrial Coupling Respiration To Copesupporting
confidence: 72%
“…The attachment of CuO ENMs to the chorion of zebrafish embryos has been demonstrated by microscopy (Böhme et al, 2017). Copper oxide ENMs have also recently been shown not to accumulate in adult zebrafish (Vicario-Parés et al, 2018). Secondly, the present study also showed greater sub-lethal effects of early exposure to CuO ENMs than CuSO 4 .…”
Section: Effects Of Pulse Exposuressupporting
confidence: 65%
“…On the other hand, cellular and molecular responses of adult zebrafish after exposure to CuO-NPs or ionic Cu were tested by Vicario-Pares et al (2018). Another study performed by Bai et al (2010) was undertaken to test the toxicity of nano-Cu suspension to zebrafish embryos.…”
Section: Toxicity On Aquatic Animalsmentioning
confidence: 99%